VH1–46 Is the Dominant Immunoglobulin Heavy Chain Gene Segment in Rotavirus-Specific Memory B Cells Expressing the Intestinal Homing Receptor α4β7 - Weitkamp, Jörn-Hendrik; Kallewaard, Nicole L.; Bowen, Amber L.; LaFleur, Bonnie J.; Greenberg, Harry B.; Crowe, James E. (The Journal of immunology (1950), 2005)
Memory B cells expressing the intestinal homing marker α4β7 are important for protective immunity against human rotavirus (RV). It is not known whether the B cell repertoire of intestinal homing B cells differs from B cells of the systemic compartment. In this study, we analyzed the RV-specific VH and VL repertoire in human IgD− B cells expressing the intestinal homing marker α4β7. The mean frequency of RV-specific B cells in the systemic compartment of healthy adult subjects was 0.6% (range, 0.2–1.2). The mean frequency of IgD− B cells that were both RV specific and α4β7 was 0.04% (range, 0.01–0.1), and a mean of 10% (range, 1–32) of RV-specific peripheral blood human B cells exhibited an intestinal homing phenotype. We previously demonstrated that VH1–46 is the dominant Ab H chain gene segment in RV-specific systemic B cells from adults and infants. RV-specific systemic IgD− or intestinal homing IgD−/α4β7+ B cells in the current study also used the gene segment VH1–46 at a high frequency, while randomly selected B cells with those phenotypes did not. These data show that VH1–46 is the immunodominant gene segment in human RV-specific effector B cells in both the systemic compartment and in intestinal homing lymphocytes. The mean replacement/silent mutation ratio of systemic compartment IgD− B cells was >2, consistent with a memory phenotype and antigenic selection. Interestingly, RV-specific intestinal homing IgD−/α4β7+ B cells using the VH1–46 gene segment were not mutated, in contrast to systemic RV-specific IgD− B cells.